2014
DOI: 10.1007/s10652-014-9376-x
|View full text |Cite
|
Sign up to set email alerts
|

Aeration and air–water mass transfer on stepped chutes with embankment dam slopes

Abstract: Stepped spillway flows are characterised by significant free-surface aeration downstream of the inception point of air entrainment. The stepped design is advantageous for applications which require large energy dissipation and strong flow aeration. While the energy dissipation rate for embankment stepped spillways was studied previously, the optimum design for aeration and air-water mass transfer is not known. Herein new air-water flow experiments were conducted on several stepped spillways with embankment dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…The range of C mean for the vegetated chutes (0.14 ≤ C mean ≤ 0.41 with an average value of C mean ≈ 0.25) compared well with observations of aerated flows on rock chutes of 0.20 ≤ C mean ≤ 0.37 for 14.8° ≤ θ ≤ 20.8° (Pagliara et al, ) and stepped chutes of 0.15 ≤ C mean ≤ 0.46 for 3.4° ≤ θ ≤ 26.6° (Felder & Chanson, ). The close agreement with previous studies on fully aerated spillway flows confirmed the significance of flow aeration in supercritical flows down vegetated slopes.…”
Section: Air‐water Flow Propertiessupporting
confidence: 80%
“…The range of C mean for the vegetated chutes (0.14 ≤ C mean ≤ 0.41 with an average value of C mean ≈ 0.25) compared well with observations of aerated flows on rock chutes of 0.20 ≤ C mean ≤ 0.37 for 14.8° ≤ θ ≤ 20.8° (Pagliara et al, ) and stepped chutes of 0.15 ≤ C mean ≤ 0.46 for 3.4° ≤ θ ≤ 26.6° (Felder & Chanson, ). The close agreement with previous studies on fully aerated spillway flows confirmed the significance of flow aeration in supercritical flows down vegetated slopes.…”
Section: Air‐water Flow Propertiessupporting
confidence: 80%
“…Near the weir crest (L/h < 15-20), the relationship between the bubble frequency and the void fraction seemed to have a good fit with the parabolic behavior reported by Toombes [35] and Brattberg et al [36] in other kinds of air-water flows. The maximum values of F/F max were obtained around C = 0.40 and 0.60 in the majority of the crosssections analyzed.…”
Section: Discussionsupporting
confidence: 72%
“…Intense turbulence, which occurs in supercritical flows, causes strong interactions between the water and the atmosphere that results in air entrainment (Pfister & Hager, 2011;Takahashi & Ohtsu, 2012). Similar to Chanson and Toombes (2004), Felder and Chanson (2015) and Toombes (2002), the flow-field measurement in the air-water mixture was conducted using a multi-tip conductivity (EC) probe. The EC probe used in this research was similar to the one used by González (2005) and Toombes (2002) with the tip diameter of 0.3 mm and had two side probes instead of one.…”
Section: Instrumentationmentioning
confidence: 99%